2016
DOI: 10.18632/oncotarget.8603
|View full text |Cite
|
Sign up to set email alerts
|

Gelsolin-mediated activation of PI3K/Akt pathway is crucial for hepatocyte growth factor-induced cell scattering in gastric carcinoma

Abstract: In gastric cancer (GC), the main subtypes (diffuse and intestinal types) differ in pathological characteristics, with diffuse GC exhibiting early disseminative and invasive behaviour. A distinctive feature of diffuse GC is loss of intercellular adhesion. Although widely attributed to mutations in the CDH1 gene encoding E-cadherin, a significant percentage of diffuse GC do not harbor CDH1 mutations. We found that the expression of the actin-modulating cytoskeletal protein, gelsolin, is significantly higher in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Gelsolin is characterized as an actin-binding protein and favors malignant progression of multiple tumor cells such as non-small lung cancer, gastric carcinoma, and glioma. 27 , 49 , 50 More importantly, several reports have indicated that Gelsolin facilitates tumor cells progression by regulating various cellular key pathways, including phosphatidylinositol 3-kinase (PI3K)/Akt and mitogen-activated protein kinase (MAPK). 50 , 51 PI3K/Akt and MAPK are two classical pathways that directly regulate cell proliferation, migration, invasion, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelsolin is characterized as an actin-binding protein and favors malignant progression of multiple tumor cells such as non-small lung cancer, gastric carcinoma, and glioma. 27 , 49 , 50 More importantly, several reports have indicated that Gelsolin facilitates tumor cells progression by regulating various cellular key pathways, including phosphatidylinositol 3-kinase (PI3K)/Akt and mitogen-activated protein kinase (MAPK). 50 , 51 PI3K/Akt and MAPK are two classical pathways that directly regulate cell proliferation, migration, invasion, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 49 , 50 More importantly, several reports have indicated that Gelsolin facilitates tumor cells progression by regulating various cellular key pathways, including phosphatidylinositol 3-kinase (PI3K)/Akt and mitogen-activated protein kinase (MAPK). 50 , 51 PI3K/Akt and MAPK are two classical pathways that directly regulate cell proliferation, migration, invasion, and apoptosis. Besides, we also found SOX5 could reverse miR-195-induced downregulation of Gelsolin, indicating that Gelsolin was involved in SNHG12/miR-195-mediated promotion of glioma cell progression.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in gelsolin expression have been associated with cigarette smoking and different pulmonary diseases such as fibrosis; however, little is known about the role of gelsolin in COPD 3234. Gelsolin activates PI3K/Akt pathway,35 which regulates cell growth, proliferation, adhesion, migration and survival. Interestingly, it promotes the differentiation of alveolar epithelial type I and II cells from alveolar epithelial stem cells 36,37…”
Section: Discussionmentioning
confidence: 99%
“…32 Alterations in gelsolin expression have been associated with cigarette smoking and different pulmonary diseases such as fibrosis; however, little is known about the role of gelsolin in COPD. [32][33][34] Gelsolin activates PI3K/Akt pathway, 35 which regulates cell growth, proliferation, adhesion, migration and survival. Interestingly, it promotes the differentiation of alveolar epithelial type I and II cells from alveolar epithelial stem cells.…”
Section: Discussionmentioning
confidence: 99%